2022
DOI: 10.3233/cbm-210446
|View full text |Cite
|
Sign up to set email alerts
|

Identifying glycolysis-related LncRNAs for predicting prognosis in breast cancer patients

Abstract: PURPOSE: Functions associated with glycolysis could serve as targets or biomarkers for therapy cancer. Our purpose was to establish a prognostic model that could evaluate the importance of Glycolysis-related lncRNAs in breast cancer. METHODS: Gene expressions were evaluated for breast cancer through The Cancer Genome Atlas (TCGA) database, and we calculated Pearson correlations to discover potential related lncRNAs. Differentially expressed genes were identified via criteria of FDR < 0.05 and |FC|> 2. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…built a signature for CRISPR-Cas9-Based Cancer Dependency Map Genes ( 52 ), and Zou et al. identified glycolysis-related lncRNAs ( 53 ); the NRlncRNA signature showed higher values of AUCs and performed better prediction of prognosis in stratified risk analysis of survival. However, we also noticed TNBC patients with a lower riskScore, which seemed not so rational.…”
Section: Discussionmentioning
confidence: 99%
“…built a signature for CRISPR-Cas9-Based Cancer Dependency Map Genes ( 52 ), and Zou et al. identified glycolysis-related lncRNAs ( 53 ); the NRlncRNA signature showed higher values of AUCs and performed better prediction of prognosis in stratified risk analysis of survival. However, we also noticed TNBC patients with a lower riskScore, which seemed not so rational.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, BC is a heterogeneous disorder that is frequently diagnosed [12]. Despite several optional BC the rapeutic strategies, there were many related deaths around the world [12].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, BC is a heterogeneous disorder that is frequently diagnosed [12]. Despite several optional BC the rapeutic strategies, there were many related deaths around the world [12]. Thus, BC analytical tools for its detection at disease early stages, as well as during its follow-up and management, are widely demanded [13].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Zou et al identified glycolysis-related lncRNAs using bioinformatics and other methods and constructed a prognostic model based on prognostic genes for breast cancer. They showed that glycolysis-related lncRNAs play an important role in facilitating individualized survival prediction in patients with breast cancer, which is a new potential prospect for breast cancer [ 92 ].…”
Section: Clinical Implications Of Targeting Glucose Metabolism In Bcmentioning
confidence: 99%